Takhrij and Syarah Hadith of Chemistry: Nabidz and Chemical Kinetics - Sari, Deti Permata; Chodijah, Siti (Research Parks Publishing LLC, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad Saw. about nabidz. The qualitative research method uses the takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this research is that nabidz water, which is the immersion of dates or raisins, is the Prophet's favorite drink. The conclusion of this research is takhrij and syarah hadith of the Prophet Muhammad Saw. About nabidz Drinks which have many benefits for the health of the body but you should not drink nabidz water that has been more than three days without preservation.